2018
DOI: 10.1093/neuros/nyy422
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study of Pipeline Flex for Intracranial Aneurysms

Abstract: The 30-d rates of neurological morbidity and mortality in this multicenter cohort using the PED Flex for the treatment of intracranial aneurysms were low, 1.9% (4/205) and 0.5% (1/205), respectively. In addition, technical events related to device deployment were also low, most likely due to the latest modifications in the delivery system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…12,19 Both devices and the Pipeline Flex Embolization Device (Medtronic, Irvine, CA) are resheathable and allow repositioning. 12,19,20 Finally, the new target to reduce thromboembolic complications is the modification of the construct surface, as observed in the Pipeline Embolization Device Flex with Shield Technology. 11 The DED (Acandis, Pforzheim, Germany) is an FD consisting of 24 wires that are looped at the closed distal end and thus result in a braid of 48 wires.…”
Section: Stroke September 2019mentioning
confidence: 99%
“…12,19 Both devices and the Pipeline Flex Embolization Device (Medtronic, Irvine, CA) are resheathable and allow repositioning. 12,19,20 Finally, the new target to reduce thromboembolic complications is the modification of the construct surface, as observed in the Pipeline Embolization Device Flex with Shield Technology. 11 The DED (Acandis, Pforzheim, Germany) is an FD consisting of 24 wires that are looped at the closed distal end and thus result in a braid of 48 wires.…”
Section: Stroke September 2019mentioning
confidence: 99%
“…It received a positive response from the interventional neuroradiology community, has an acceptable safety profile, and has a high rate of successful aneurysm occlusion. 5 , 6…”
Section: Introductionmentioning
confidence: 99%
“…The PED Flex device is the second refined version approved in 2015 to address the disadvantages of the previous-generation device, with improved releasing system, improved resheathing capability, and modified pusher wire ( 42 , 43 ). Studies have shown improved clinical outcomes of the PED Flex device, with decreases in the surgical time, technical failure, and procedural complications ( 44 46 ). With the development of science and technology, flow diverters may be further refined, and the risk profile of flow diverters may be decreased over the years with newer iteration of the devices, resulting in better clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%